2023
DOI: 10.1186/s13578-023-00968-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding protein SAMD4: current knowledge and future perspectives

Abstract: SAMD4 protein family is a class of novel RNA-binding proteins that can mediate post-transcriptional regulation and translation repression in eukaryotes, which are highly conserved from yeast to humans during evolution. In mammalian cells, SAMD4 protein family consists of two members including SAMD4A/Smaug1 and SAMD4B/Smaug2, both of which contain common SAM domain that can specifically bind to different target mRNAs through stem-loop structures, also known as Smaug recognition elements (SREs), and regulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…For example, Galns and Samd4a have been implicated in neuronal viability and plasticity; Galns that encodes a lysosomal exohydrolase has been considered a gene related to Parkinson's disease (Wettergren et al, 2012) and Samd4a is a RNA binding protein that can bind to a variety of target mRNAs through stem-loop structures, also known as Smaug recognition elements (SREs). Notably, Samd4a can regulate the mRNA stability, degradation and translation (Wang and Zhang, 2023). Fgr (Gardner-Rasheed feline sarcoma viral (v-fgr) oncogene homolog) and Psmb9 (proteasome subunit beta type-9), two innate immunity genes, both of which were affected by CHMA1004 treatment, each were recently associated with specific genetic forms of Parkinson's disease (Shani et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Galns and Samd4a have been implicated in neuronal viability and plasticity; Galns that encodes a lysosomal exohydrolase has been considered a gene related to Parkinson's disease (Wettergren et al, 2012) and Samd4a is a RNA binding protein that can bind to a variety of target mRNAs through stem-loop structures, also known as Smaug recognition elements (SREs). Notably, Samd4a can regulate the mRNA stability, degradation and translation (Wang and Zhang, 2023). Fgr (Gardner-Rasheed feline sarcoma viral (v-fgr) oncogene homolog) and Psmb9 (proteasome subunit beta type-9), two innate immunity genes, both of which were affected by CHMA1004 treatment, each were recently associated with specific genetic forms of Parkinson's disease (Shani et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…SAMD4 is an RBP with the role of protein translational repressor. It is mostly involved in the regulation of post-transcription events, including mRNA stability, and translational repression during early bone embryonic development ( Wang and Zhang, 2023 ). In vivo experiments in mice ( Niu et al, 2017 ) with a depletion of the Samd4 gene, have shown profound defects in both skeleton development and bone mass; compared to WT mice, KO Samd4 mice were characterized by impaired bone ossification and mineralization.…”
Section: Physiological Roles Of Rbps In Bone Cellsmentioning
confidence: 99%
“…Primary osteoblasts collected from both KO Samd4, cultured under osteoblast differentiation medium, showed impaired of both early and late osteoblast differentiation when compared to those from WT mice. SAMD4 acts by inhibiting the translation of Mitogen-inducible gene 6 (Mig6) protein, a non-kinase scaffolding adaptor strongly expressed in osteoblasts, through binding the 3′UTR ( Staal et al, 2014 ; Wang and Zhang, 2023 ).…”
Section: Physiological Roles Of Rbps In Bone Cellsmentioning
confidence: 99%
“…SAMD4A, also known as Smaug1 in Drosophila, is a conserved RBP encoded by the SAMD4A gene 52 . Accumulating evidence highlighted the importance of SAMD4A in cell differentiation and developmental diseases 53 . For instance, depletion of SAMD4A leads to developmental defects in mice such as delayed bone development and reduced osteogenesis by inhibiting the translation of Mig6 32 .…”
Section: ➢ Mrna Stability Functions As a Buffering System Between Tra...mentioning
confidence: 99%